Tingkat Kondisi Fisik Pemain Sepakbola Porprov Kabupaten Pati - Ahmad Badawi; Sumarjo; Abdul Alim (Universitas Singaperbangsa, 2021)
The purpose of the study was to determine the level of physical condition of the provincial football players in Pati district. This type of research is descriptive. The sample used was 20 players. Instrument speed sprint 60 meters, endurance using a multistage fitness test, agility using the Illinois test, leg muscle explosive power using a standing board jump. The results obtained from the speed test, there were 15 players in the good category (75%), 5 players in the sufficient category (25%), the endurance test there were 14 players in the sufficient category (70%), 5 players in the less category by (25%) and 1 player in the very poor category (5%), agility test there was 1 player in the good category by (5%), 19 players entered the sufficient category (95%) and the leg muscle explosive power test contained 4 players fall into the moderate category (20%), 16 players fall into the less category (80%).